Nelumbo nucifera Gaertn: An updated review of the antitumor activity and mechanisms of alkaloids - Po Hu; Xiao Ge; Ming-Tong Gao; Xin-Zhu Wang; Ying-Ying Zhang; Yun Li; Jing Xiao; Ye-Wen Ni; Qing-Long Guo; Yang Pan (Elsevier, 2022)
Nelumbo nucifera Gaertn. is an aquatic plant in the family Nelumbonaceae, and almost every part has medicinal uses. It has been established that alkaloids are one of the main components in N. nucifera. This review focuses on the traditional uses of N. nucifera, the alkaloid constituents in each part of the plant and their structural classification, providing a comprehensive overview of the profiles of alkaloids isolated from N. nucifera and their antitumor activities. The efficiency and molecular mechanism of the alkaloids against specific tumors are reported, and their effects are discussed according to the hallmarks of cancer, highlighting their significance during cancer treatment. Furthermore, with the discovery of a new structural type of tribenzylisoquinolines alkaloid, neoliensinine, the antitumor effect of alkaloids in N. nucifera can be inferred from the structure of isoquinolines. This review aims to provide a theoretical basis for further development of natural products and new therapeutic agents in clinical practice and research on the mechanism of alkaloids in N. nucifera.